Phenotype shift from atypical scrapie to CH1641 following experimental transmission in sheep. - Marion M Simmons; S Jo Moore; Richard Lockey; Melanie J Chaplin; Timm Konold; Christopher Vickery; John Spiropoulos (PLoS ONE)
The interactions of host and infecting strain in ovine transmissible spongiform encephalopathies are known to be complex, and have a profound effect on the resulting phenotype of disease. In contrast to classical scrapie, the pathology in naturally-occurring cases of atypical scrapie appears more consistent, regardless of genotype, and is preserved on transmission within sheep homologous for the prion protein (PRNP) gene. However, the stability of transmissible spongiform encephalopathy phenotypes on passage across and within species is not absolute, and there are reports in the literature where experimental transmissions of particular isolates have resulted in a phenotype consistent with a different strain. In this study, intracerebral inoculation of atypical scrapie between two genotypes both associated with susceptibility to atypical forms of disease resulted in one sheep displaying an altered phenotype with clinical, pathological, biochemical and murine bioassay characteristics all consistent with the classical scrapie strain CH1641, and distinct from the atypical scrapie donor, while the second sheep did not succumb to challenge. One of two sheep orally challenged with the same inoculum developed atypical scrapie indistinguishable from the donor. This study adds to the range of transmissible spongiform encephalopathy phenotype changes that have been reported following various different experimental donor-recipient combinations. While these circumstances may not arise through natural exposure to disease in the field, there is the potential for iatrogenic exposure should current disease surveillance and feed controls be relaxed. Future sheep to sheep transmission of atypical scrapie might lead to instances of disease with an alternative phenotype and onward transmission potential which may have adverse implications for both public health and animal disease control policies.